Analysis of Low Cost Carrier Implementation and Service Quality on Customer Satisfaction and Passenger Loyalty of Citilink Airlines - Elschilera Caesar Thoranya; Aisyah Rahmawati; Aditya Wardhana (Jurnal Ilmu Multidisiplin, 2025)
The purpose of this research project is to clarify how consumer satisfaction and customer loyalty are influenced by the deployment of lowcost carriers and service quality. This study uses a sample of 98 LowCost Carrier Citilink users using a quantitative methodology. A questionnaire was utilized in the survey, and SmartPLS 4.0 software was employed for analysis. The study found that while service quality and the use of low-cost carriers had a major impact on consumer satisfaction, they had no direct effect on customer loyalty. In the link between the use of low-cost carriers and service quality to customer loyalty, customer satisfaction plays a key mediating role.